(untitled) (Recoletos Multidisciplinary Research Journal, 2025)
Background: Eggshell powder (ESP) is a widely studied alternative to cement due to its chemical similarity to lime. Prior research has shown that up to 15% ESP replacement can improve compressive strength, and some findings show improvement even at 20% replacement levels. Methods: This study used an experimental design approach was used. Mortar specimens were prepared with varying ESP and carrot nanofiber (CNF) proportions. The samples were cured under standard conditions and tested for compressive strength after 28 days. Results: Among the tested combinations, the mix with 35% ESP and 0.30%-wt CNF achieved the highest compressive strength. However, this strength remained below the reference strength of the traditional control mix, which measured 7.5 MPa. Conclusion: While the combination of ESP and CNF improved compressive strength relative to other experimental groups, it did not meet the performance of the traditional cement mix. Further research is required to refine the parameters and fully utilize the potential of these alternative materials in cement reduction.